Utilization of Geological Wealth of Celebes Canyon Tourism Area, Libureng Village, Tanete Riaja District, Barru Regency - Sirajuddin, Haerany; Pachri, Hendra; Imran, A. M.; Langkoke, Rohaya; ., Kaharuddin; ., Sultan; Burhanuddin, Safri; ., Bahrul; Halide, Lidemar; A., Dwi Nuraeni; Jannah, A. Mifthahul (Faculty of Engineering UNHAS, 2024)
The development of the tourist area in Celebes Canyon, Libureng Village, Tanete Riaja District, Barru Regency, has enormous potential in utilizing the geological wealth of the area, where the rocks resemble the Grand Canyon in America. Community service activities in Libureng Village aim to provide understanding and socialize the utilization of the geological wealth of Celebes Canyon to the community living around the tourist area, in this case as community service partners, as well as identifying the challenges and opportunities in developing this tourist destination. With an inclusive approach, it is hoped that Celebes Canyon will not only be a tourist attraction, but also provide economic and social benefits to the surrounding community. The method used in this LBE (Laboratory Based Education) community service activity is to conduct observations aimed at obtaining systematic data on the objects to be socialized and continued with socialization activities to the Libureng village community. Based on the results of the observation, it was found that the development of facilities and infrastructure around the tourist attraction needs to be carried out to maintain the geological potential and natural beauty and reduce environmental damage, besides that it is also necessary to always maintain cleanliness around the tourist area. During the socialization activity, a pre-test was conducted on 20 local residents regarding the potential and utilization of geological wealth, as well as the importance of maintaining the environment around the tourist area, the results showed that the level of understanding was in the range of 15% - 42%, but the post-test showed an increase in understanding of 22% - 67%. The importance of cooperation between various stakeholders to create a harmonious partnership in managing tourist attractions; as well as improving the quality of human resources from both managers and local communities is very much needed to support the development of sustainable tourist attractions.